A new technology for estimating time shifts in seismic monitoring of the exploitation of oil and gas fields and underground gas storage sites - Yu. K. Tyapkin; O. Yu. Tiapkina (Геофизический журнал, 2018)
The process of exploitation of oil and gas fields and underground natural gas and CO2 storage facilities is accompanied by time-dependent changes in the physical properties of both the reservoir itself and the overburden. The study of these changes via time lapse (4D) seismic allows controlling the efficiency of operation of oil and gas fields and underground gas storage facilities. A wide class of methods uses, as intermediate information, time shifts arising in time lapse seismic data when studying the changes in the geomechanical properties of a reservoir. In this paper, conditions are formulated under which the values of the reflection coefficients of boundaries when changing the properties of a medium are preserved, but shifted to a new position along the two-way traveltime axis. To assess the time shifts that arise in this way, a new technology is developed. It is based on the statistical properties of the cross-correlation function of two time-limited random processes one of which is a shifted and stretched or compressed in time variant of the other. The proposed technology allows the constant and linear components of the time shifts to be determined simultaneously when the number of accumulated cross-correlation functions of such processes is sufficient. The validity of the theoretical foundations of the method is confirmed by two numerical experiments. As a source of input data required for the application of this technology in practice, it is suggested to use a random component of seismic images generated by chaotic fluctuations in the acoustic impedance in the lower half-space. Some methods for approximating the regular component of seismic records are described. Subtracting this component from the record allows its random component, which is necessary for the implementation of the proposed technology in practice, to be obtained.